Method development and validation for rapid extraction and identification of solanaceous alkaloids present in Chinese herbs. - Lim, Xinyi. (2009)
Solanaceous alkaloids have been listed as poisons under the Schedule of the Poisons Act (Chapter 234) in Singapore. According to Health Sciences Authority’s (HSA) health supplements guidelines published on November 2008, such substances are not allowed in health supplements. Hence, analysis of these products is essential to ensure the safety of the public. Prior to analysis, extraction of these compounds is required, but current extraction methods are time-consuming and tedious. Thus, a rapid & effective extraction method is needed. An automated extraction method using Accelerated Solvent Extractor (ASE) had been optimized for the extraction of solanidine and solasodine in Bulbus Fritillariae Thunbergii (BFT) and Solanum Nigrum Linne (SNL) respectively. Optimized conditions for solanidine were solvent, methanol; temperature, 80oC; flush volume, 60%; heat, 5 min; static time, 5 min and static cycle, 3. The total extraction time was 19 minutes. For solasodine, optimization was still in the midst, but solvent and temperature were selected as dichloromethane and 120oC respectively. The method for solanidine was also validated based on linearity, limit of detection (LOD), limit of quantification (LOQ), precision, specificity, recovery yield and extraction completeness. This optimized and validated method allowed rapid extraction of solanidine and offered the possibility of faster and more efficient analysis of health supplements for the presence of solanidine.